Sociology of food consumption in Algeria - Saib, Bouzid (The International tax journal, 2025)
This research paper examines food culture in Algerian society, particularly given the following: - There are several attempts to regulate food supply chains; - The recent rise in the incidence of chronic diseases and their association with modern nutrition; - There are contemporary consumer models resulting from the media and cultural invasion; - The connection between social life and cultural heritage. The researcher used the descriptive approach and statistical analysis to answer the following questions: - Is there a statistically significant relationship between socio-cultural indicators and an individual's nutritional and health status? In this study, we sought to highlight the relationship between culture, nutrition, and health, as well as their relationship to income indicators and the frequency and types of food consumption. This is through the first stage, in which bibliographic readings allowed us to define concepts and present the various stages of Algerian cultural development, which is directly related to daily nutritional and health practices. Finally, we present the field study that collected 30 individuals from the residents of the city of Algiers, and we used an interview form as a basic tool in collecting data.